An uncertain target-oriented QFD approach to service design based on service standardization with an application to bank window service. (2nd November 2019) - Yan, Hong-Bin; Meng, Xiang-Sheng; Ma, Tieju; Huynh, Van-Nam
Abstract: This article proposes an uncertain target-oriented QFD approach to service standardization-based service design with an application to bank window service, based on a probabilistic interpretation of weighting information. On the one hand, the proposed approach performs computations solely based on the order-based semantics of linguistic labels and comparisons of linguistic profiles, without needing to quantify the qualitative concepts. It can thus guarantee the robustness of QFD and easy of use in practice. On the other hand, the proposed approach sets uncertain targets for customer needs (WHATs) and service standards (HOWs) by competitors' uncertain service performance on WHATs and HOWs, and conducts satisfactory-oriented competitive analysis from the perspective of uncertain target-oriented decision analysis. Moreover, the proposed approach is applied to an empirical case study of window service design based on service standardization in the Shanghai Branch of Bank JT. The results show that the bank should pay more attention to "Service specifications", "Service providing specifications", and "Service evaluation and improvement standards". Industry feedback shows that the results are consistent with service acceptance and provide valuable insights to the service standardization in the bank. Comparisons with existing studies show that our proposed approach is comparable with existing studies.